Consumer Perceptions towards Online Retailing in Botswana: A Case Study of the University of Botswana - Dzimiri, Mashoko Tserere; Thamage, Katlego Asher; Mapharing, Mogotsinyana; Basuhi, Elang; Radikoko, Ishmael (Discoveries in Agriculture and Food Sciences, 2018)
The study was premised on assessing the existing customer perceptions towards online retailing in Botswana. In particular, the study used University of Botswana staff and students as a case study. Data for this study was collected through questionnaires given to students and staff of the University of Botswana. Descriptive statistics and Independent t-tests were used to analyse the results. The results from this study indicate that consumers in the University of Botswana utilise traditional shopping more than online shopping. Though accessible by people of all income, online shopping is perceived to be risky and needs a skillful internet user. Delivery concerns, technology specific innovativeness and financial risk were found to negatively influence online shopping behavior. On the other hand, subjective norms, good return policy and convenience were found to positively influence online shopping behavior. The findings from this study provide a first glance at existing customer perceptions in Botswana which should encourage further and more extensive research to yield more generalizable results that reflect consumer perceptions. Local retailers or businesses will find these results useful as these will help them narrow their focus on how to sway consumers to use their online shops.